Light-curing process for clear aligners' attachment reproduction: comparison between two nanocomposites cured by the auxiliary of a new tool - Francesca Gazzani; Denise Bellisario; Fabrizio Quadrini; Carlotta Danesi; Andrea Alberti; Paola Cozza; Chiara Pavoni (BMC, 2022)
Abstract Background Attachments' configuration play an important role during Clear Aligner Treatment (CAT) for aligner retention and control of movements planned. The aims were to compare the macroscopic morphology of attachments reproduced with flowable (FNC) and conventional (CNC) composites and the effects on them of two light-guide tips with different dimensions. Methods 4 resin casts derived from the initial scan of the same patient were obtained. 10 vestibular attachments were replaced on both upper and lower arches of each model with CNC (Models A, B) and FNC (Models C, D). Each composite was cured by means of the same LED lamp with both regular light-guide (Models A, B) and push and light tool® (Models C, D). The 80 attachments were qualitative analyzed by means of a digital stereo microscope. Surface roughness and waviness measurements were assessed by contact probe surface profiler (TalySurf CLI 2000; Taylor Hobson, Leicester, United Kingdom). Statistical analysis was performed with independent samples t-tests. Significance was established at the P < 0.05 level. Results Model A showed lower values of surface roughness (Ra − 1.41 µm, Rt − 3.46 µm) and waviness (Wa − 2.36 µm, Wt − 10.95 µm) when compared with Model C. Significant reduction of waviness (Wa − 3.85 µm, Wt − 4.90 µm) was observed on Model B when compared with Model D. Significant increase of roughness and waviness parameters (Ra 3.88 µm, Rt 21.07, Wa 2.89 µm, Wt 14.74 µm) was found when CNC sample (Model A) was cured with regular light-guide tip. Higher values (Ra 2.33 µm, Rt 24.07 µm, Wa 1.67 µm, Wt 20.79 µm) were observed after regular light-guide tips curing on FNC sample (Model C). Conclusions CNC resins determine more regular surfaces of attachments profiles. The additional use of a smaller light- guide of the LED push and light tool® allows to improve the macroscopic morphology of the attachments and to maximize light irradiance delivering by enhancing the polymerization process and the integrity of the features during the treatment.